2017
DOI: 10.1038/nature23286
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of ground-state female ES cells maintaining gamete-derived DNA methylation

Abstract: Inhibitors of Mek1/2 and Gsk3β, known as 2i, enhance the derivation of embryonic stem (ES) cells and promote ground-state pluripotency in rodents. Here we show that the derivation of female mouse ES cells in the presence of 2i and leukaemia inhibitory factor (2i/L ES cells) results in a widespread loss of DNA methylation, including a massive erasure of genomic imprints. Despite this global loss of DNA methylation, early-passage 2i/L ES cells efficiently differentiate into somatic cells, and this process requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
237
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(261 citation statements)
references
References 47 publications
23
237
1
Order By: Relevance
“…The difference in DNA methylation stability between hESCs and the embryo might not be restricted to human cells, as two recent reports showed that naive mouse ESCs lose their imprints when cultured in media containing MEK1/2 inhibitor [20,21]. These studies contrast with several previous reports that demonstrated imprint stability, and the reasons for the discrepant findings are not obvious.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…The difference in DNA methylation stability between hESCs and the embryo might not be restricted to human cells, as two recent reports showed that naive mouse ESCs lose their imprints when cultured in media containing MEK1/2 inhibitor [20,21]. These studies contrast with several previous reports that demonstrated imprint stability, and the reasons for the discrepant findings are not obvious.…”
contrasting
confidence: 55%
“…These studies contrast with several previous reports that demonstrated imprint stability, and the reasons for the discrepant findings are not obvious. Loss of imprints in mouse ESCs might be associated with defective developmental potential [20,21], although this needs to be examined more systematically and also in the context of naive hESC differentiation.…”
mentioning
confidence: 99%
“…Indeed, ectopic expression of Dnmt3a or Dnm3b can rescue the reduced methylation levels at particular regions in female ES cells. 76 74,78 These results suggest that female-specific hypomethylation is in part caused by impaired maintenance of DNA methylation due to two active X chromosomes. It is also interesting that female ES cells tend to lose all or part of one X chromosome during their propagation, while male ES cells occasionally lose Y chromosome, indicating that female ES cells are genetically unstable.…”
Section: Epigenetic and Genetic Instability In Female Mouse Es Cellsmentioning
confidence: 71%
“…However, it has not been fully elucidated whether genetic and epigenetic stabilities of 2i-treated ES cells are stable. Recent studies demonstrated that derivation of ES cells directly from blastocysts in 2i/LIF and prolonged culture of ES cells in 2i/LIF result in loss of DNA methylation at imprinted loci 74,75 (Figure 4). Surprisingly, such imprint eroded ES cells compromise autonomous developmental potential by tetraploid embryo complementation and nuclear transfer 74,75 (Figure 4).…”
Section: Capturing Ground State In Vitro By Modulating Extrinsic Signmentioning
confidence: 99%
See 1 more Smart Citation